Motoristas de plataformas digitais: uma leitura a partir do trabalho na cidade de Ituiutaba/MG - Oliveira, Fábia Riza de Andrade (2024)
The world of work has changed over the years according to the objects and techniques available to modify the geographic space and the way of production. The first division of labor began when men hunted and women took care of the crops. Then, with the Industrial Revolution, there was the division of labor in factories. Each process for manufacturing a product was the responsibility of certain people, who did not know the other steps, as was done by artisans. With the advent of the internet and modern technologies that have globalized the world, physical space is no longer an impediment to conducting paid activities. Many of them started to be conducted digitally. Companies have emerged that have developed digital platforms to coordinate the work of people in the crowd work system, in which the requesters represent the people who need the service and the digital platforms bring together supply and demand and the workers who offer it in the same place. the services. Added to these facts are the urban mobility problems faced by people. Currently, more dispersed and fragmented cities generate a large flow of trips and public transport is often not sufficient to meet this demand. “Uberização”, considered a new form of work organization, assumes its role in crowd work. With a discourse of solving urban mobility problems, this gave rise to the class of workers that are the object of this research: passenger transport drivers added to digital platforms. In addition, the recent COVID-19 pandemic is considered, which changed the lives of the world population and brought social isolation as one of the contingency measures for the disease. The general objective of this research is to understand the work of passenger transport drivers on digital platforms that operate in the city of Ituiutaba/MG. To achieve this, the following specific objectives are to characterize the platforms that operate in the city of Ituiutaba/MG, with a parallel to the working conditions they offer; identify the working conditions of passenger transport drivers on digital platforms operating in the city of Ituiutaba/MG; and research how the impacts of the COVID-19 pandemic have affected this category. Descriptive and bibliographical research was conducted. The approach used was qualitative/quantitative. Semi-structured interviews were conducted with 20 drivers. Among other aspects, several forms of precarious work to which this group is subjected daily were identified. However, even with this adverse situation, many have no other alternative, they see this activity as temporary, because as Ricardo Antunes says, “any work is better than no work” and bread needs to be guaranteed.